2021
DOI: 10.7181/acfs.2020.00472
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of anemia and micronutrient deficiency among children with cleft lip and palate: a single-center cross-sectional study from Uttarakhand, India

Abstract: Background Children with cleft lip and/or palate can be undernourished due to feeding difficulties after birth. A vicious cycle ensues where malnutrition and low body weight precludes the child from having the corrective surgery, in the absence of which the child fails to gain weight. This study aimed to identify the proportion of malnutrition, including the deficiency of major micronutrients, namely iron, folate and vitamin B 12 , in children with cleft lip and/or palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, the prevalence of malnutrition in CP and CLP infants, reported by Tungotyo et al in Uganda, was 68% with 57% having moderate-to-severe malnutrition. The factors that were associated with malnutrition in this study were caretakers lacking nutritional information post-delivery, low birth weight, and having less than 10 feeds in 24 hours [6]. Thus, breastfeeding education and assistance are critical for adequate infant nutrition.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the prevalence of malnutrition in CP and CLP infants, reported by Tungotyo et al in Uganda, was 68% with 57% having moderate-to-severe malnutrition. The factors that were associated with malnutrition in this study were caretakers lacking nutritional information post-delivery, low birth weight, and having less than 10 feeds in 24 hours [6]. Thus, breastfeeding education and assistance are critical for adequate infant nutrition.…”
Section: Discussionmentioning
confidence: 80%
“…Postpartum, the first week of infancy, is associated with a decrease in body weight that is followed by a gradual increase at a rate of 500-700 g per week. However, in clinical scenarios, children with facial clefts often remain undernourished due to maternal malnourishment, feeding difficulties, and recurrent upper respiratory infections that can have a catabolic effect [3]. Additional fortified supplements are often necessary for these infants to enhance their overall growth and development.…”
Section: Role Of Weightmentioning
confidence: 99%
“…The "rule of 10" formulated by Wilhelmsen et al in 1966 was the first published guideline that defined the timing of cleft lip repair [1]. This was later modified by Millard (1976) and is now used all over the world [2][3]. As per the rule of 10, a cleft lip can be repaired in infants at 10 weeks of age with hemoglobin levels of 10 gm%, an average weight of 10 pounds, and a total count of leucocytes of 10,000 cells/cc.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found that children with disabilities were three times more likely to be underweight and twice as likely to be stunted or wasted than non-disabled children [6]. Children with disabilities are more likely to be overweight or obese [6] or anemic [7]. They are twice as likely as non-disabled children to die from malnutrition [2].…”
Section: Introductionmentioning
confidence: 99%